Hybrid laser arc welding: State-of-art review. (1st February 2018) - Acherjee, Bappa
Highlights: This paper presents a systematic review of hybrid laser arc welding process. Hybrid laser arc welding utilizes synergic effects of laser welding and arc welding. The hybrid laser arc welding process is 50–100% faster than the laser welding. High welding speed and deep penetration make this process economical than laser welding. The growing numbers of industrial applications proved the potential of commercial use. Abstract: Hybrid laser arc welding simultaneously utilizes the arc welding and the laser welding, in a common interaction zone. The synergic effects of laser beam and eclectic arc in the same weld pool results in an increase of welding speed and penetration depth along with the enhancement of gap bridging capability and process stability. This paper presents the current status of this hybrid technique in terms of research, developments and applications. Effort is made to present a comprehensive technical know-how about this process through a systematic review of research articles, industrial catalogues, technical notes, etc. In the introductory part of the review, an overview of the hybrid laser arc welding is presented, including operation principle, process requirements, historical developments, benefits and drawbacks of the process. This is followed by a detailed discussion on control parameters those govern the performance of hybrid laser arc welding process. Thereafter, a report of improvements of performance and weld qualities achieved by using hybrid welding process is presented based on review of several research papers. The succeeding sections furnish the examples of industrial applications and the concluding remarks.